Community Radio a Social Tool for Women Enpowerment in Namakkal District (International Journal of Emerging Trends in Science and Technology, 2017)
This paper presents an insight into a proposal that intends to empowerment of women. It reflects on directand indirect impacts of the initiative that targeted hundreds of women in Paramathi Velur, NamakkalDistrict. The major aim of this paper is to promote social and economic empowerment of women. The keyfactors are that the ability of women to attaining knowledge and creation, personal and communitydevelopment and as a whole women‟s development in the society. The research also examines the recentimprovements in radio broadcast coverage and the information providing the women with a platform thatadequately meets their needs.